HELICOBACTER PYLORI INFECTION IN CHILDREN: SITE-SPECIFIC DISTRIBUTION, ANTIBIOTIC RESISTANCE AND OPTIMIZATION OF THERAPEUTIC PROTOCOLS (Journal of Multidisciplinary Sciences and Innovations, 2025)
Helicobacter pylori infection in children remains a significant global health concern due to its association with gastritis, peptic ulcer disease, and potential long-term sequelae such as gastric malignancy. Early and accurate diagnosis requires optimal biopsy site selection, while rising antibiotic resistance challenges eradication success. This study reviews site-specific distribution of H. pylori colonization in the pediatric stomach, evaluates contemporary antibiotic resistance patterns, and proposes optimization strategies for therapeutic protocols. We conducted a prospective multicenter observational study from January 2022 to December 2024, enrolling children aged 3–18 years undergoing diagnostic endoscopy for upper gastrointestinal symptoms. Biopsies were obtained from the gastric antrum and corpus for histology, culture with antibiotic susceptibility testing, and molecular resistance detection. Resistance rates were determined for clarithromycin, metronidazole, amoxicillin, levofloxacin, and tetracycline. Treatment regimens were tailored based on susceptibility results or, when unavailable, according to regional resistance prevalence. Among 150 enrolled children, 60 (40%) were confirmed H. pylori–positive. Antral colonization was detected in 95% of positives versus 70% in the corpus (p85% eradication in most groups; empirical regimens aligned with resistance prevalence also attained acceptable success (>80%) when clarithromycin was avoided in regions with >15% resistance. We recommend obtaining multiple antral biopsies plus at least one corpus biopsy for optimal detection and culture, routine susceptibility testing where feasible, and therapeutic algorithms that reflect local resistance data in accordance with recent pediatric guidelines. Ongoing surveillance and individualized therapy protocols are essential to maximize eradication rates and minimize antibiotic misuse.